Cold induced genes (CIGs) regulate flower development and dormancy in Prunus avium L. (December 2021) - Wang, Jiyuan; Liu, Xunju; Sun, Wanxia; Xu, Yan; Sabir, Irfan Ali; Abdullah, Muhammad; Wang, Shiping; Jiu, Songtao; Zhang, Caixi
Highlights: We cloned PavCIG1/2 from sweet cherries, and observed a delayed flowering phenotype in transgenic Arabidopsis . PavCIG2 integrated temperature, light and ABA signaling to regulate flower development and dormancy. PavCIG1/2 target gene PavCAL-like was involved in floral initiation, demonstrated by ectopic expression in Arabidopsis . Abstract: The flower buds continue to develop during the whole winter in tree fruit species, which is affected by environmental factors and hormones. However, little is known about the molecular mechanism of flower development during dormancy phase of sweet cherry in response to light, temperature and ABA. Therefore, we identified two cold induced gene ( CIG ) PavCIG1 and PavCIG2 from sweet cherry, which were closely to PpCBF and PyDREB from Prunus persica and Prunus yedoensis by using phylogenetic analysis, suggesting conserved functions with these evolutionarily closer DREB subfamily genes. Subcellular localization analysis indicated that, PavCIG1 and PavCIG2 were both localized in the nucleus. The seasonal expression levels of PavCIG1 and PavCIG2 were higher at the stage of endodormancy in winter, and induced by low temperature. Ectopic expression of PavCIG1 and PavCIG2 resulted in a delayed flowering in Arabidopsis . Furthermore, PavCIG2 increased light-responsive gene PavHY5 transcriptional activity by binding to its promoter, meanwhile, PavHY5-mediated positive feedback regulated PavCIG2 . Moreover, ABA-responsive protein PavABI5-like could also increase transcriptional activity of PavCIG and PavCIG2 . In addition, PavCIG and PavCIG2 target gene PavCAL-like was involved in floral initiation, demonstrated by ectopic expression in Arabidopsis . These findings provide evidences to better understand the molecular mechanism of CIG-mediated flower development and dormancy in fruit species, including sweet cherry.